WTX R353X mutation in a family with osteopathia striata and cranial sclerosis (OS-CS): case report and literature review of the disease clinical, genetic and radiological features - Zicari Anna; Tarani Luigi; Perotti Daniela; Papetti Laura; Nicita Francesco; Liberati Natascia; Spalice Alberto; Salvatori Guglielmo; Guaraldi Federica; Duse Marzia (BMC, 2012)
Abstract Osteopathia striata with cranial sclerosis (OS-CS) or Horan-Beighton syndrome is a rare X-linked dominant inherited bone dysplasia, characterized by longitudinal striations of long bones and cranial sclerosis. Patients can be asymptomatic or present with typical facial dysmorphism, sensory defects, internal organs anomalies, growth and mental retardation, depending on the severity of the disease. WTX gene (Xq11) has been recently identified as the disease causing gene. Aim of this article is to present the case of a 6 year old girl initially evaluated for bilateral hearing loss. Patient's head CT scan pointed out sclerosis of skull base and mastoid cells, and abnormal middle-ear ossification. Clinical examination of the patient and her mother were suspicious for OS-CS. The diagnosis was confirmed by X-rays examination showing typical longitudinal striation. Genetic analysis allowed the identification of maternally transmitted heterozygous nonsense c.1057C>T (p.R353X) WTX gene mutation. We also provide a systematic review of currently available knowledge about clinical, radiologic and genetic features typical of the OS-CS.